IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE PICTURE AND PICTURE DALAM MENINGKATKAN HASIL BELAJAR IPA: SDN TANAHWULAN 01 KECAMATAN MAESAN KABUPATEN BONDOWOSO (Dewan Pendidikan Bondowoso, 2020)
The purpose of this study was to describe the implementation of learning and to determine the percentage level of student learning completeness in the material of motion tools and their functions in animals and humans by using the picture and picture cooperative learning model in class Vb SDN Tanahwulan 01, Maesan sub-district, Bondowoso regency, 2017/2018 academic year. . This type of research is a classroom action research conducted with two cycles and each cycle there are two meetings. Data were obtained using research instruments in the form of observation sheets and written tests which were analyzed using qualitative descriptive analysis techniques. The indicator of the success of this classroom action research uses the predetermined minimum completeness criteria (KKM), namely ≥ 65 with classical completeness of 91% or 21 students. The result of this research can be concluded that the use of picture and picture cooperative learning model can improve the learning outcomes of learning science subject matter of motion and its function in animals and humans. This can be seen from the results of the analysis of each indicator in this study increasing sharply from the initial conditions until after the action was taken. The increase in learning outcomes is marked by the completeness of learning in cycle 1 obtained above the KKM as much as 18 or 78% and in cycle 2 as much as 23 or 100%.